Boosting oxygen reduction reaction activity of palladium by stabilizing its unusual oxidation states in perovskite - Zhu, Y.; Zhou, W.; Chen, Y.; Yu, J.; Xu, X.; Su, Chao; Tadé, M.; Shao, Zongping (American Chemical Society, 2015)
The high cost, scarcity, and poor stability of metallic platinum (Pt) as an oxygen reduction reaction (ORR) catalyst in fuel cells and metal-air batteries have limited the commercialization of these attractive clean-energy technologies. Thus, developing alternative electrocatalysts that are economical and achieve maximized efficiency of stably catalyzing ORR is of prime importance in the societal pursuit of sustainable energy. Metallic palladium (Pd) is an alternative electrocatalyst that is less expensive than Pt; however, its current performance remains insufficient. Here we report for the first time that the ORR activity of the different oxidation states of Pd increased in the following order: Pd0 < Pd2+ < perovskite-type ionic (Pi) Pd3/4+. Especially, the intrinsic activity on Pd active site of (Pi) Pd3/4+ is ~84-fold higher than that of Pd0. By doping the Pd element as a cation into the perovskite oxide lattice to form LaFe0.95Pd0.05O3-δ and LaFe0.9Pd0.1O3-δ, unusual oxidation states of 3/4+ for Pd are stabilized, and the catalysts exhibit superior mass activity, durability, and tolerance to methanol compared with the benchmark commercial Pt/C catalyst.